A Thousand Years of Christianity in Phrygia - McKechnie, Paul 1957-; Mitchell, Stephen 1948-2024 (2025)
This review article centers on the research contribution made by Stephen Mitchell’s The Christians of Phrygia from Rome to the Turkish Conquest. After a brief summary of previous work on the subject, Mitchell’s coverage is outlined and his solutions to some historical problems examined—in the light of Ramsay MacMullen’s conception of the (Roman) epigraphic habit.
Keywords: Byzantine; Hagiography; Epigraphy; Montanism; Aberkios; Phrygia; Early Christianity; Rezension